Method for synthesizing pyruvic acid by photocatalytic reforming of PLA (polylactic acid) and application
By using Pd/CdS-supported catalysts during PLA photocatalytic reforming, the CdS is excited by using visible light to generate electrons and holes, achieving high selectivity conversion of PLA to pyruvate and H2, and solving the PLA photoreduction in the prior art The problem of low overall selectivity has achieved efficient and environmentally friendly resource utilization.
Patent Information
- Application Number
- CN202310989095.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-18
AI Technical Summary
The existing PLA photoreforming routes are less selective due to complex side reactions, making it difficult to efficiently recover and convert them into high value-added chemicals.
Pd/CdS-supported catalyst is used to photocatalytically reform PLA into pyruvate under visible light irradiation, and electrons and holes are generated through photoexcitation of CdS, inhibit electron-hole pair recombination, and promote PLA hydrolysis and oxidation to generate pyruvate.
Highly selective photocatalytic reforming of PLA is achieved, high value-added pyruvate is generated, and clean energy H2 is generated, solving the environmental problems caused by waste PLA and improving the efficiency of resource utilization.
Smart Images

Figure CN119455983A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of photocatalysis, and specifically comprises a method and application of photocatalytic reforming of PLA to synthesize pyruvic acid. Background Art
[0002] In recent years, with the rapid development of the plastic, rubber and fiber industries based on petroleum, the amount of energy stored on the earth has been decreasing and the problem of environmental pollution has become more and more serious. How to solve these pollutions and develop natural degradable alternative materials has become an important research goal for countries around the world in recent years. Polylactic acid (PLA) is an excellent bio-based polymer material with good biocompatibility and biodegradability. It can be widely used in industries such as industry, packaging and medicine. However, with the rapid growth of PLA production and consumption, the amount of waste PLA is increasing, which has become a new problem affecting environmental pollution. Although PLA can be degraded under natural conditions, its degradation process in the real environment is actually very slow. Waste stacking or landfilling will occupy space and pollute the environment. In addition, even if it is finally degraded, the products are CO2 and H2O. This is not only a CO2 emission process that leads to a large carbon footprint, but also a waste of carbon resources. Therefore, while continuously strengthening the research on the preparation technology of PLA materials, the research on the recycling technology of waste PLA has also received increasing attention. An effective PLA recycling method is urgently needed to produce high value-added chemicals.
[0003] At present, the photoreforming recovery route of PLA has made great progress in concept and method, but it is limited by complex side reactions that lead to reduced selectivity, such as: over-oxidation reaction to produce CO2, decarboxylation reaction to produce acetic acid, cracking reaction to produce formic acid, etc. Therefore, it is of great significance to develop a more selective photoreforming route for PLA. Summary of the invention
[0004] In view of the above problems existing in the prior art, an object of the present invention is to provide a method for synthesizing pyruvic acid by photocatalytic reforming of PLA. The method synthesizes high-value-added pyruvic acid from PLA through the photocatalytic action of a Pd / CdS supported catalyst under visible light irradiation, has the advantages of mild reaction conditions, simple operation, high visible light utilization rate, high product added value, etc., and exhibits high application value.
[0005] Another object of the present invention is to provide a new application of the method as described above in the photocatalytic reforming of PLA to prepare pyruvic acid.
[0006] To achieve the above first object, the technical solution adopted by the present invention includes:
[0007] The present invention discloses a method for synthesizing pyruvic acid by photocatalytic reforming of PLA, comprising the following steps:
[0008] S1, mixing an aqueous solution or aqueous dispersion containing PLA with a photocatalyst to obtain a reaction solution;
[0009] S2, irradiating the reaction solution with visible light to obtain;
[0010] Wherein, the photocatalyst is selected from Pd / CdS supported catalyst.
[0011] In the present invention, under visible light irradiation, CdS is excited to generate electrons and holes at the conduction band and valence band, respectively. Since PLA acts as a hole acceptor to suppress the recombination of electron-hole pairs, the excited electrons can be effectively transferred to the surface of Pd to reduce H2O to H2. The lactic acid generated by the hydrolysis of PLA will be oxidized by the photogenerated holes to a high value-added organic product (i.e., pyruvic acid). Therefore, the reaction can achieve the synergistic production of hydrogen and pyruvic acid.
[0012] Further, the mass ratio of the PLA to the photocatalyst is 100-700:1; illustratively, the mass ratio of the PLA to the photocatalyst can be 100:1, 200:1, 300:1, 400:1, 500:1, 600:1, 700:1, and the like.
[0013] Furthermore, the loading amount of Pd in the photocatalyst is 0.5-5.0wt%; exemplarily, the loading amount of Pd in the photocatalyst can be 0.5wt%, 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% and the like.
[0014] Furthermore, the photocatalyst provided by the present invention can be prepared by referring to the preparation process disclosed in the prior art, such as the CdS nanospheres obtained by the hydrothermal method, the precipitation method and the ion exchange method, and the catalytic performance exhibited in the subsequent photocatalytic reaction is equivalent. In a specific embodiment, the inventor first prepares the CdS nanospheres by the precipitation method, and then loads Pd on the CdS nanospheres by the sodium borohydride reduction method. The photocatalyst is prepared according to the following steps:
[0015] (1) Preparation of CdS nanospheres by precipitation method
[0016] Dissolve the Cd-containing compound in water and adjust the pH to neutral with aqueous ammonia;
[0017] Slowly add thioacetamide, and then adjust the pH to alkaline with ammonia water to completely hydrolyze the thioacetamide; after the reaction is completed, CdS nanospheres are obtained;
[0018] (2) Preparation of Pd / CdS supported catalyst by sodium borohydride reduction method
[0019] The Na2PdCl4 solution is added into the prepared CdS nanospheres, and then the sodium borohydride solution is added dropwise to obtain a Pd / CdS supported catalyst.
[0020] Furthermore, the Cd-containing compound includes but is not limited to one or more of CdCl2, Cd(NO3)2, and Cd(CH3CO2)2.
[0021] In the preparation of CdS nanospheres, ammonia water is used for pH adjustment because ammonia water can better control thioacetamide to achieve controlled hydrolysis, thereby achieving control over the reaction.
[0022] Furthermore, the specific surface area of CdS nanospheres prepared by the precipitation method is 1-100m 2 g -1 , preferably 10-100m 2 g -1 .
[0023] Furthermore, before the reaction of step S2 is started, the reaction liquid is also deoxygenated and sealed. For example, the deoxygenation method may be to use argon to purge the reaction liquid for more than 20 minutes to remove oxygen in the reaction liquid; the sealing method may use a rubber diaphragm to seal the reaction liquid.
[0024] Furthermore, the concentration of the aqueous solution or aqueous dispersion containing PLA is 10-200 mg mL -1 .
[0025] Further, the aqueous solution containing PLA is prepared according to the following steps:
[0026] The commercially purchased PLA was pre-hydrolyzed by hydrothermal treatment at 140-160°C for 8-12 h to obtain an aqueous solution containing PLA.
[0027] Furthermore, the PLA-containing aqueous dispersion is prepared according to the following steps:
[0028] The PLA product is crushed into PLA powder with a mesh size of 60-200 mesh, and then water is added and mixed to form an aqueous dispersion containing PLA.
[0029] Furthermore, the visible light irradiation time is 1-100 hours; preferably, when the reaction substrate is an aqueous solution containing PLA, the reaction substrate is in a uniform solution state due to hydrolysis, and the required reaction time is short, so the visible light irradiation time is 1-12 hours. When the reaction substrate is an aqueous dispersion containing PLA, the photocatalyst reacts slowly with the PLA powder, and the required reaction time is long, so the visible light irradiation time is 10-100 hours.
[0030] Furthermore, the light source of visible light is selected from one or more of LED, high pressure mercury lamp, medium pressure mercury lamp, xenon lamp and sunlight.
[0031] To achieve the above second purpose, the technical solution adopted by the present invention includes:
[0032] The present invention discloses an application of the above method in preparing pyruvic acid by photocatalytic reforming of PLA.
[0033] Beneficial effects of the present invention:
[0034] The invention discloses a method for synthesizing pyruvic acid by photocatalytic reforming of PLA. The method utilizes the strong photocatalytic activity of a Pd / CdS supported catalyst to efficiently and selectively synthesize PLA into high-value-added pyruvic acid, while generating clean energy H2. This method can not only solve a series of environmental problems caused by waste polylactic acid, but also produce high-value-added products, thus realizing the process of solid waste resource utilization and having high application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] The specific implementation modes of the present invention are further described in detail below in conjunction with the accompanying drawings.
[0036] Figure 1 The X-ray diffraction pattern and transmission electron microscopy image of the CdS nanospheres prepared in Preparation Example 1 are shown;
[0037] in, Figure 1 a is the X-ray diffraction pattern, and b is the transmission electron microscope image.
[0038] Figure 2 The N2 adsorption-desorption curve of the CdS nanospheres prepared in Preparation Example 1 is shown.
[0039] Figure 3 The X-ray diffraction pattern and transmission electron microscopy image of the Pd / CdS supported catalyst prepared in Preparation Example 2 are shown;
[0040] in, Figure 3 a is the X-ray diffraction pattern, and b is the transmission electron microscope image. DETAILED DESCRIPTION
[0041] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0042] The visible light source used in the following embodiments is a xenon lamp with a wavelength of 400-800 nm, a model of Beijing Perfect-light Co. Ltd, PLS-SXE300D, and a power of 150-300 W.
[0043] Preparation Example 1
[0044] Preparation of CdS nanospheres by precipitation method
[0045] 1 mmol CdCl2·2.5H2O was dissolved in 100 mL deionized water, and the pH was adjusted and controlled to 7.0 using aqueous ammonia, and then TAA solution (1 mmol TAA was dissolved in 20 mL deionized water) was slowly dripped into the solution with pH = 7.0. After the addition of TAA was completed, the pH was adjusted to 10.0 using aqueous ammonia to ensure complete hydrolysis of TAA, and an orange suspension was obtained;
[0046] The orange suspension was stirred for 2 h and transferred to a centrifuge tube, washed with deionized water several times, and then freeze-dried overnight to obtain CdS nanospheres. The X-ray diffraction pattern and transmission electron microscopy image of the prepared CdS nanospheres are shown in Figure 1 As shown, the N2 adsorption and desorption curve is as follows Figure 2 As shown in Figure 2, the specific surface area of the obtained CdS nanospheres is 12.91 m 2 g -1 .
[0047] Preparation Example 2
[0048] Preparation of Pd / CdS Supported Catalyst by Sodium Borohydride Reduction
[0049] First, 30 mg of the CdS nanospheres of Preparation Example 1 were added, dispersed by ultrasonication for 10 min, and then 165 μL of 10 mg / mL Na2PdCl4 solution was added dropwise, followed by 1 mL of 4 mg / mL sodium borohydride solution to prepare 2.0 wt% of metal Pd loaded on the CdS nanospheres. The metal-loaded CdS nanospheres were then transferred to a centrifuge tube, washed several times with deionized water, and then freeze-dried overnight for subsequent catalytic tests.
[0050] The X-ray diffraction pattern and transmission electron microscopy image of the prepared Pd / CdS supported catalyst are shown in Figure 3 shown.
[0051] Preparation Example 3-7
[0052] The same method as in Preparation Example 2 was used to prepare supported catalysts in which Pt, Rh, Ru, Ag or Ni were supported on CdS nanospheres, respectively, to obtain supported catalysts with different metal loads.
[0053] 2.0wt% of different metals (Pt, Rh, Ru, Ag and Ni) were loaded on CdS nanospheres by NaBH4 chemical reduction using corresponding metal cation aqueous solutions. The metal-loaded CdS nanospheres were then transferred to a centrifuge tube, washed several times with deionized water, and then freeze-dried overnight for subsequent catalytic testing.
[0054] Example 1
[0055] This example is the photocatalytic reforming of an aqueous solution containing PLA using a Pd / CdS supported catalyst.
[0056] Commercially purchased PLA particles were hydrothermally treated at 150 °C for 10 h for pre-hydrolysis to obtain a PLA aqueous solution;
[0057] Add 5 mg of the photocatalyst prepared in Preparation Example 2 to a 60 mL quartz tube, and then add 20 mL of 100 mg mL -1 The PLA-containing aqueous solution was ultrasonically treated for 10 min, and then stirred at 50°C (1000 r / min) to obtain a reaction solution;
[0058] The reaction solution was purged with Ar for at least 20 min to remove O2, then sealed with a rubber septum and sampled after irradiation under a xenon lamp for 8 h. The chromatograph was performed by Shimadzu GC-2014C (Ar carrier gas, molecular sieve The amount of evolved hydrogen was determined by a thermal conductivity detector (TCD) and the amount of organic oxidation products was quantitatively determined by a 600 MHz nuclear magnetic hydrogen spectrum. The results are shown in Table 1.
[0059] Comparative Examples 1-6
[0060] The experimental process is the same as that of Example 1, except that the catalysts prepared in Preparation Example 1 and Preparation Examples 3-7 replace the photocatalyst of Example 1, and other experimental conditions are the same as those of Example 1. The results obtained are shown in Table 1.
[0061] Table 1
[0062] sample Hydrogen production / μmol Pyruvate production / μmol Pyruvate selectivity / % Example 1 736 618 84 Comparative Example 1 110 0 0 Comparative Example 2 200 147 74 Comparative Example 3 550 306 56 Comparative Example 4 238 182 76 Comparative Example 5 116 0 0 Comparative Example 6 232 0 0
[0063] Example 2
[0064] This example is the photocatalytic reforming of an aqueous solution containing PLA using a Pd / CdS supported catalyst.
[0065] The preparation process of the aqueous solution containing PLA is the same as that in Example 1.
[0066] Add 5 mg of the photocatalyst prepared in Preparation Example 2 to a 60 mL quartz tube, and then add 20 mL of 100 mg mL -1The PLA-containing aqueous solution was ultrasonically treated for 10 min, and then stirred at 50°C (1000 r / min) to obtain a reaction solution;
[0067] The reaction solution was purged with Ar for at least 20 min to remove O2, then sealed with a rubber septum, sampled after irradiation under a xenon lamp for a certain period of time, and the amount of hydrogen evolved was determined by Shimadzu GC-2014C gas chromatography, and the amount of organic oxidation products was quantitatively detected by 600 MHz nuclear magnetic hydrogen spectrum. The results are shown in Table 2. After 12 h of reaction, the selectivity of pyruvic acid was 86%.
[0068] Table 2
[0069]
[0070]
[0071] Example 3
[0072] This example is the photocatalytic reforming of a water dispersion containing PLA using a Pd / CdS supported catalyst.
[0073] Commercially available PLA tableware (produced by Chaoyue Co., Ltd.) was frozen in liquid nitrogen and crushed into 80-mesh PLA powder, and water was added to prepare 100 mg mL -1 The dispersion is set aside.
[0074] 20 mg of the photocatalyst prepared in Preparation Example 2 was added to a 60 mL quartz tube, followed by 20 mL of 100 mg mL -1 The prepared dispersion was ultrasonically treated for 10 min, and then stirred at 50° C. (1000 r / min) to obtain a reaction solution;
[0075] The reaction solution was purged with Ar for at least 20 min to remove O2, and then sealed with a rubber septum. After irradiation under a xenon lamp for a certain period of time, samples were taken, and the amount of hydrogen released was determined by Shimadzu GC-2014C gas chromatography, and the amount of organic oxidation products was quantitatively detected by 600 MHz nuclear magnetic hydrogen spectrum. The results are shown in Table 3. After 100 h of reaction, almost no other liquid products were found, and the selectivity of pyruvic acid was close to 100%.
[0076] Comparative Example 7
[0077] Commercially available PLA tableware (produced by Chaoyue Co., Ltd.) was frozen in liquid nitrogen and crushed into 80-mesh PLA powder, and water was added to prepare 100 mg mL -1 The dispersion was ultrasonically treated for 10 min and stirred at 50°C (1000 r / min) to obtain a reaction solution;
[0078] The reaction solution was purged with Ar for at least 20 min to remove O2, and then sealed with a rubber septum. After irradiation under a xenon lamp for 10 h, samples were taken and the amount of hydrogen evolved was determined by Shimadzu GC-2014C gas chromatography. The amount of organic oxidation products was quantitatively detected by 600 MHz nuclear magnetic hydrogen spectrum. The results are shown in Table 3.
[0079] Comparative Example 8
[0080] Commercially available PLA tableware (produced by Chaoyue Co., Ltd.) was frozen in liquid nitrogen and crushed into 80-mesh PLA powder, and water was added to prepare 100 mg mL -1 The dispersion is set aside.
[0081] Add 110 μL of 10 mg / mL Na2PdCl4 solution to a 60 mL quartz tube, then add 20 mL of 100 mg / mL -1 The prepared dispersion was ultrasonically treated for 10 min, and then stirred at 50° C. (1000 r / min) to obtain a reaction solution;
[0082] The reaction solution was purged with Ar for at least 20 min to remove O2, and then sealed with a rubber septum. After irradiation under a xenon lamp for 10 h, samples were taken and the amount of hydrogen evolved was determined by Shimadzu GC-2014C gas chromatography. The amount of organic oxidation products was quantitatively detected by 600 MHz nuclear magnetic hydrogen spectrum. The results are shown in Table 3.
[0083] Comparative Example 9
[0084] Commercially available PLA tableware (produced by Chaoyue Co., Ltd.) was frozen in liquid nitrogen and crushed into 80-mesh PLA powder, and water was added to prepare 100 mg mL -1 The dispersion is set aside.
[0085] 20 mg of the photocatalyst prepared in Preparation Example 2 was added to a 60 mL quartz tube, followed by 20 mL of 100 mg mL -1 The prepared dispersion was ultrasonically treated for 10 min, and then stirred at 50° C. (1000 r / min) to obtain a reaction solution;
[0086] The reaction solution was purged with Ar for at least 20 min to remove O2, and then sealed with a rubber septum. After reacting for 10 h in a dark environment, samples were taken and the amount of hydrogen evolved was determined by Shimadzu GC-2014C gas chromatography, and the amount of organic oxidation products was quantitatively detected by 600 MHz nuclear magnetic hydrogen spectrum. The results are shown in Table 3.
[0087] Table 3
[0088]
[0089] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.
Claims
1. A method for synthesizing pyruvic acid by photocatalytic reforming of PLA, characterized in that: The steps include: S1, mixing an aqueous solution or aqueous dispersion containing PLA with a photocatalyst to obtain a reaction solution; S2, irradiating the reaction solution with visible light to obtain; Wherein, the photocatalyst is selected from Pd / CdS supported catalyst.
2. The method according to claim 1, characterized in that The mass ratio of the PLA to the photocatalyst is 100-700:
1.
3. The method according to claim 1, characterized in that The loading amount of Pd in the photocatalyst is 0.5-5.0 wt %.
4. The method according to claim 1, characterized in that: The concentration of the aqueous solution or aqueous dispersion containing PLA is 10-200 mg mL -1 .
5. The method according to claim 1, characterized in that: Before the reaction in step S2 begins, the reaction liquid is deoxygenated and sealed.
6. The method according to claim 1, characterized in that The light source of the visible light is selected from one or more of LED, high pressure mercury lamp, medium pressure mercury lamp, xenon lamp and sunlight.
7. The method according to claim 1, characterized in that The visible light irradiation time is 1-100h.
8. The method according to claim 1, characterized in that The PLA-containing aqueous solution is prepared according to the following steps: The PLA particles are hydrothermally treated at 140-180° C. for 8-12 hours for pre-hydrolysis to obtain an aqueous solution containing PLA.
9. The method according to claim 1, characterized in that: The PLA-containing aqueous dispersion is prepared according to the following steps: The PLA product is crushed into PLA powder with a mesh size of 60-200 mesh, and then water is added and mixed to form an aqueous dispersion containing PLA.
10. Use of the method according to any one of claims 1 to 9 in preparing pyruvic acid through photocatalytic reforming of PLA.